COVID‐19 Fueled an Elevated Number of Human‐Caused Ignitions in the Western United States During the 2020 Wildfire Season - Jorge, Adam L.; Abatzoglou, John T.; Fleishman, Erica; Williams, Emily L.; Rupp, David E.; Jenkins, Jeffrey S.; Sadegh, Mojtaba; Kolden, Crystal A.; Short, Karen C. (Earth's future, 2025)
The area burned in the western United States during the 2020 fire season was the greatest in the modern era. Here we show that the number of human‐caused fires in 2020 also was elevated, nearly 20% higher than the 1992–2019 average. Although anomalously dry conditions enabled ignitions to spread and contributed to record area burned, these conditions alone do not explain the surge in the number of human‐caused ignitions. We argue that behavioral shifts aimed at curtailing the spread of COVID‐19 altered human‐environment interactions to favor increased ignitions. For example, the number of recreation‐caused wildfires during summer was 36% greater than the 1992–2019 average; this increase was likely a function of increased outdoor recreational activity in response to social distancing measures. We hypothesize that the combination of anomalously dry conditions and COVID‐19 social disruptions contributed to widespread increases in human‐caused ignitions, adding complexity to fire management efforts during the 2020 western US fire season. Knowledge of how social behavior changes indirectly contributed to the increased number of ignitions in the 2020 wildfire season can help inform resource management in an increasingly flammable world. Plain Language Summary Aggregated fire records show that the 2020 wildfire season in the western United States resulted in both the greatest burned area in recent decades and one of the greatest numbers of human‐caused fires since 1992, despite a 30‐year low in the number of lightning‐caused fires. While the record area burned has largely been attributed to climate and weather conditions favorable to wildfire, we show that climate alone is unlikely to be responsible for the spike in human‐caused fires. Instead, we suggest that changes in human behavior and mobility during the COVID‐19 pandemic facilitated increases in the number of human‐caused fires in 2020 against a backdrop of longer‐term declines in human‐caused fires. We show that ways in which people responded to the pandemic, such as by sheltering in place and social distancing, potentially contributed to increases in the number of ignitions caused by debris burning, recreation, and use of fireworks. For example, increased outdoor recreation—a social distancing measure—during summer 2020 contributed to a 36% increase in the number of recreation‐caused fires. Although we focus on the 2020 fire season, our results inform understanding of complex human‐natural system interactions in places with escalating fire danger. Key Points The 2020 fire season in the western United States experienced one of the highest number of human‐caused ignitions in nearly 3 decades Climate variability was weakly correlated with ignitions; non‐climatic factors drove the near record number of human‐caused ignitions Increased human presence in wildlands due to COVID‐19 behavioral changes contributed to increased in human‐caused fires